Systematic Review: The Role of Video Analysis in Improving Basic Football Skills - Ardiansyah, Mohamad Ilham; Galih, Restu; Huda, Syamsul Nurul; Sepmiar, Zhona Alfarizi; Nurrachmad, Limpad (STKIP Taman Siswa Bima, 2025)
This systematic review examines the role of video-based media, including video tutorials, video feedback, interactive videos, video tests, and motion analysis software, in improving basic football (soccer) technical skills. Basic skills such as passing, dribbling, shooting, and ball control require accurate visual understanding to support effective motor learning and error correction. A systematic literature search was conducted using Google Scholar databases, focusing on peer-reviewed articles related to video-based learning and performance analysis in sports. A total of 20 relevant studies met the inclusion criteria. The findings consistently show that video-based interventions positively influence technical accuracy, movement understanding, learning motivation, decision-making ability, and overall performance quality. Video feedback was identified as the most effective approach for correcting technical errors, while motion analysis software such as Kinovea proved valuable for biomechanical evaluation, particularly in shooting techniques. This review concludes that video analysis is an effective and relevant learning strategy for coaches and educators to enhance mastery of basic football skills across educational and training contexts.